2020
DOI: 10.1088/1367-2630/ab6cde
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of electric quadrupole and magnetic quadrupole coupling in a symmetric silicon structure

Abstract: Multipole interferences have attracted a lot of interests in last decade due to extraordinary performance on beam control and scattering shaping. However, most of previous works focused on the dipole-based interferences while the quadrupole modes and other high-order multipole modes with unique properties were of less attention. In this work, we aim to expand the present dipole-based multipole-interference regime to the quadrupole-interference regime. We study the interference between an electric quadrupole (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…16 Multipolar resonances are more complex and are described elsewhere. 17 The reflectance response of the RS metasurfaces are qualitatively like that of the other three. There is a very strong similarity between y-polarised RS spectra for 160 to 210 nm thick substrates and those from the other arrays.…”
Section: Reflectance Spectramentioning
confidence: 79%
See 1 more Smart Citation
“…16 Multipolar resonances are more complex and are described elsewhere. 17 The reflectance response of the RS metasurfaces are qualitatively like that of the other three. There is a very strong similarity between y-polarised RS spectra for 160 to 210 nm thick substrates and those from the other arrays.…”
Section: Reflectance Spectramentioning
confidence: 79%
“…The more dominant M Q contributions for the thicker sample can be rationalised by considering that the magnetic components of the resonances are parallel to the incident light excitation, therefore, as the silicon depth is increased, M Q is better supported across the height of the structures. 17…”
Section: Resultsmentioning
confidence: 99%
“…Their presence creates destructive interference in the far-field , due to resonance frequency matching of electric and magnetic Mie type multipoles. Usually, this is achieved by tuning the dimensions in symmetric and asymmetric structures …”
Section: Resultsmentioning
confidence: 99%
“…Usually, this is achieved by tuning the dimensions in symmetric and asymmetric structures. 49 Different from the anapole state, the observed modal distribution can also be described by the Mie scattering theory. Murphy and Brueck showed that the magnetic dipole resonance wavelength is proportional to the product of the refractive index, n, of the particle and its diameter D so that λ MD = nD.…”
Section: Optical Properties Of Sinc Supported Au-np Arraysmentioning
confidence: 99%
“…ED + MD Silicon spherical nanoparticles 55,63 -ED + EQ Plasmonic gold nanoring nanoantenna 25 -ED + MQ -Ceramic spheroidal particle 64 Silicon square nanoplate 62 MD + EQ -Core-shell SiO2@InSb and Si@InSb in a one-dimensional (1D) metalattice geometry in the Terahertz range 65 MD + MQ Ceramic core-shell 66 -EQ + MQ Both isolated and periodically arranged homogeneous cross dielectric structure 67 -ED + MD + EQ + MQ Individual core-shell nanoparticles 68 Silicon cube 29 Ceramic cube and cylinder 30 Vol:. ( 1234567890) www.nature.com/scientificreports/ than the EQ and MD.…”
Section: Generalized Transversementioning
confidence: 99%